TECHNICAL REVIEW OF OPERATIONAL PATTERNS OF THE WEST FLOOD CHANNEL MOVEMENT (KBB) IN SEMARANG CITY - Nugroho, Eko Pudjo; Ni'am, M. Faiqun; Soedarsono, Soedarsono (AGUSPATI Research Institute, 2021)
A based on the concept of the convenience of the West Flood Canal (KBB) river in Semarang City which is divided into five zones, so in 2019 work on the construction of the KBB Motion Weir was held. To optimize the operation of the Mobile Weir, it is necessary to analyze and simulate the operational pattern of the KBB Mobile Weir. The aim is to obtain procedures and patterns in the operation of mobile dams and the right and efficient opening and closing times during the rainy season and during sediment flashing. In this study, hydraulic analysis was used with the help of the HEC-RAS 4.1.0 program. to track flooding in the river channel using mathematical modeling in several scenarios. From this analysis, it can be seen how far the procedures and operational patterns of the West Flood Canal Movement Weir (KBB) are in accordance with several planned scenarios. The results of the study found that the simulation of the opening of 1 (one) door/span using Qmax 220.71 m3/second, as scenario I in the Standby/Ready condition. Simulation of opening 1 (one) door/span using Qmax 339.81 m3/second, according to scenario II during Standby II/Standby conditions. And scenario III for Saga III/Beware) requires 4 (four) door openings/span.